Productivity Analysis in the Production Process Using the Six Sigma Method (Case Study at the XSMK Company) - Elanjati Worldailmi (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
XSMK company is a company engaged in the furniture sector that produces various kinds of shelving products in Indonesia. There are problems that hinder the productivity of the company, namely waste in the production process. Six Sigma is an organized and systematic method for process improvement strategy and new product development that relies on statistical methods and scientific methods to create reductions in product defect rates. With the Six Sigma method, the company implements a vision of quality improvement towards the target of 3.4 failures per million opportunities DPMO (Defects Per Million Opportunities). For this reason, a study was conducted which aimed to determine the value of six sigma, the causes of product rejects, as well as suggestions for improvements to the company. From the results of data processing, the company has an average sigma level of 4,336 with a possible damage of 5,867.5 units for one million productions. There are 4 out of 11 processes that cause rejected products, namely Pond, Bending Plate, Spot, Welding. The main cause of Reject is plate Bending with the percentage of total Reject being 48.077%. From the problems that occur, actions can be taken to minimize Reject products in the production process at the company in the form of making improvements to the Pond Process, Plate Bending Process, Spot Process, Welding Process, Machines, Workers, Raw Materials, and Systems that exist in the company.